2022
DOI: 10.1016/j.jconrel.2022.01.008
|View full text |Cite
|
Sign up to set email alerts
|

Non-viral vectors for RNA delivery

Abstract: RNA-based therapy is a promising and potential strategy for disease treatment by introducing exogenous nucleic acids such as messenger RNA (mRNA), small interfering RNA (siRNA), microRNA (miRNA) or antisense oligonucleotides (ASO) to modulate gene expression in specific cells. It is exciting that mRNA encoding the spike protein of COVID-19 (coronavirus disease 2019) delivered by lipid nanoparticles (LNPs) exhibits the efficient protection of lungs infection against the virus. In this review, we introduce the b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
100
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 156 publications
(136 citation statements)
references
References 295 publications
0
100
0
1
Order By: Relevance
“…The currently available systems for the efficient delivery of miRNA include non-viral vectors and viral vectors. The non-viral miRNA delivery system uses organic, inorganic or polymer-based carriers, whereas a viral-based delivery system usually uses lentiviruses, retroviruses, adenoviruses and adeno-associated viruses [ 159 , 160 ].…”
Section: Mirna Delivery Systemsmentioning
confidence: 99%
“…The currently available systems for the efficient delivery of miRNA include non-viral vectors and viral vectors. The non-viral miRNA delivery system uses organic, inorganic or polymer-based carriers, whereas a viral-based delivery system usually uses lentiviruses, retroviruses, adenoviruses and adeno-associated viruses [ 159 , 160 ].…”
Section: Mirna Delivery Systemsmentioning
confidence: 99%
“…On the basis of a previous study, vitamin A was grafted via the synthesis of DSPE-PEG 2k -VA and mainly distributed on the surface of the nanoparticles because of the hydrophilic property of the PEG chain. siCol1α1 was absorbed onto the surface via electrostatic interaction, and the positive charge of amines would be masked by the negative charge of phosphate groups in siRNA . Collagenase I was modified on the basis of the covalent interaction between maleimide in DSPE-PEG 2k -Mal and the sulfydryl group in thiolated collagenase I (SH-collagenase I) and mainly distributed on the surface of the nanoparticles.…”
Section: Resultsmentioning
confidence: 99%
“…siCol1α1 was absorbed onto the surface via electrostatic interaction, and the positive charge of amines would be masked by the negative charge of phosphate groups in siRNA. 39 Collagenase I was modified on the basis of the covalent interaction between maleimide in DSPE-PEG 2k -Mal and the sulfydryl group in thiolated collagenase I (SHcollagenase I) and mainly distributed on the surface of the nanoparticles. Agarose gel retardation assays revealed that siRNA combined completely with C 15 −PA at a weight ratio of 1:5 and combined completely with CV-NPs at a weight ratio of 1:10 (Figure S4A).…”
Section: Resultsmentioning
confidence: 99%
“…A distinctive feature of nucleic acid molecules is that they are negatively charged; therefore, they can be adsorbed to cationic carriers and delivered into cells. However, nonviral carriers can potentially be toxic and show lower cellular uptake than viral vectors [ 42 ]. Finally, some physical methods, such as gene guns, electroporation, and laser irradiation, deliver naked nucleic acids into the cells.…”
Section: Versatile Engineering Strategiesmentioning
confidence: 99%